2011
DOI: 10.1089/end.2010.0382
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Penile Length After Robot-Assisted Laparoscopic Radical Prostatectomy

Abstract: This report describes changes in SPL over time after RALRP for prostate cancer. The expected decrease in length was observed shortly after surgery, but, by 9 months, penile length had returned to the preoperative measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 20 publications
3
45
1
Order By: Relevance
“…We were unable to find other studies about the impact of postoperative penile shortening on quality of life and self-esteem among prostate cancer survivors (other than a comment from Engel et al 12 that studies concerning this topic would be desirable). That self-perceived penile shortening seems to affect quality of life and self-esteem in prostate cancer survivors to a greater degree than in the control group might be attributable to the control group probably having had a longer period of time to cope with their self-perceived penile shortening than the operated group where onset can be thought to be more sudden.…”
Section: Radical Prostatectomy S Carlsson Et Almentioning
confidence: 92%
See 2 more Smart Citations
“…We were unable to find other studies about the impact of postoperative penile shortening on quality of life and self-esteem among prostate cancer survivors (other than a comment from Engel et al 12 that studies concerning this topic would be desirable). That self-perceived penile shortening seems to affect quality of life and self-esteem in prostate cancer survivors to a greater degree than in the control group might be attributable to the control group probably having had a longer period of time to cope with their self-perceived penile shortening than the operated group where onset can be thought to be more sudden.…”
Section: Radical Prostatectomy S Carlsson Et Almentioning
confidence: 92%
“…They stated that this non-operated group of men already had end-organ (penis) changes from their longstanding ED. Recently, Engel et al, 12 in a study of 127 patients after robot-assisted radical prostatectomy, found a median penile shortening of 0.64 cm 1 month postoperatively, but found that after 9 months penile length had returned to the preoperative measurement. They concluded that penile shortening could be a surrogate measure of erectile function after a radical prostatectomy.…”
Section: Radical Prostatectomy S Carlsson Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that SPL measurements have been reported to strongly correlate with those for erect PL (Wessells et al, 1996), SPL measurements of PL have been adopted in many studies (Munding et al, 2001;Savoie et al, 2003;Gontero et al, 2007;Haliloglu et al, 2007;Engel et al, 2011;Park et al, 2011;Vasconcelos et al, 2012;Berookhim et al, 2014;Kadono et al, 2017). Considering that SPL measurements have been reported to strongly correlate with those for erect PL (Wessells et al, 1996), SPL measurements of PL have been adopted in many studies (Munding et al, 2001;Savoie et al, 2003;Gontero et al, 2007;Haliloglu et al, 2007;Engel et al, 2011;Park et al, 2011;Vasconcelos et al, 2012;Berookhim et al, 2014;Kadono et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…24 In a study by Engel et al, 3 the stretched penile length was measured before and after bilateral nerve-sparing RP and showed a significant decrease in length from 11.77 to 11.13 cm at 1 month. In a similar study by Savoie et al, 4 in which penile length was measured before and after retropubic RP, significant decreases were seen for the flaccid and stretched measurements and circumference.…”
Section: Commentmentioning
confidence: 99%